Profil of omega-3 food intake and its association with socioeconomic status in smoker on online motorcycle drivers - Amelia Lorensia; Rivan Virlando Suryadinata (PAGEPress Publications, 2023)
Introduction: Omega-3 fatty acids were found to be effective in reducing inflammation and free radicals caused by air pollution (cigarette smoke), as well as improving lung function. Furthermore, economic conditions can influence a person's food consumption habits. The type of food consumed will certainly affect the amount of omega-3 absorbed by the body, and the quality of food consumed is influenced by socioeconomic status (SES). Therefore, the purpose of this study was to determine omega-3 intake and its relationship with the socioeconomic status of online motorcycle drivers. Design and Methods: This was an observational study with a cross-sectional method of measuring omega-3 consumption using a 24-hour food recall questionnaire and assessing the mean of omega-3 intake after 3 days. The was conducted from May-August 2020, in Kali Rungkut, Surabaya City, and the subjects were online motorcycle drivers. A Chi-square test was used to assess the relationship between omega-3 intake and SES (income and education). Results: There were 49 respondents in this study with most of them having a classification of omega-3 intake at the deficit level (57.14%), and none belonging to the good and more level. There was a significant difference in omega-3 intake on income (p=0.000) and education (p=0.000). Conclusions: Income and education must be prioritized to improve a healthy diet that includes omega-3.